Evaluation of the serum levels of tumor necrosis factor-alpha in Iraqi patients with autoimmune thyroid disorders: a study from the Najaf Governorate - M. Almayahi, Thikra A.; Y. Al-Timimi, Thikra G.; Al-Muhanna, Estabraq H.; Alzaml, Alaa H. O.; Al-Juaifari, Ali N. A. (Pharmakeftiki, 2025)
Thyroid disorders frequently arise due to iodine deficiency or autoimmune conditions. Autoimmune thyroid disorders, such as Graves’ disease (GD) and Hashimoto’s thyroiditis (HT), result from dysregulation of the immune system. In this study, a total of 140 samples were analysed using immunodiagnostic methods. Participants were divided into two groups: 70 healthy controls and 70 patients (35 diagnosed with GD and 35 with HT), all recruited from medical facilities in the Najaf Governorate (Iraq) between July and October 2023. Participant ages ranged from 20 to over 50 years. Thyroid hormone levels – triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH) – were measured in order to classify cases as hypothyroid or hyperthyroid. Results showed significantly reduced levels of T3, T4, and TSH in patients with hypothyroidism. On the other hand, the levels of anti-thyroglobulin (anti-TG) and anti-thyroid peroxidase (anti-TPO) antibodies were markedly elevated in patients with HT or with GD compared to the control group. HT was more prevalent among women aged 30 to 50 years. Smoking was found to be significantly associated with the presence of thyroid disorders. A notable difference in mean tumor necrosis factor-alpha (TNF-α) concentrations was observed between patients with GD and the control group, whereas no significant difference was found for patients with HT. The study concludes that TNF-α levels vary significantly between autoimmune thyroid conditions, underscoring its potential role in disease pathogenesis.